Actors and Audiences: Negotiating Fisheries Management. Issue 4 (7th August 2016) - Boucquey, Noëlle C.
Abstract : This paper combines narrative and policy performance analyses to explore why resource management is contentious even when resources are increasing in abundance. Employing a case study of red drum in North Carolina, the study aimed to find out how different narratives of fishery science interact with policy performances to create outcomes that exacerbate conflicts. Examining six years of fisheries governance, the study explores how policy performances shape managers' interpretations of fisheries science and modes of interacting with each other. The study finds that despite being a so-called success story, red drum management remains controversial because while user groups are concerned about access and allocation questions, managers focus on debating the meaning and implications of scientific data. Though compromises between user groups are made, conflict continues because the process through which they are reached creates frustration rather than understanding. That resource access dilemmas remain so prominent confirms that continually increasing scientific information has done little to solve resource conflicts, a key point in the dawning era of 'big data'. The findings underscore the need for more scrutiny of how policy-making is performed, to provide insight into where interventions might promote better collaboration and acceptance of compromises.